Examining International Postgraduate Student Reflections of Intensive and Semester Modes of Delivery - Liu, Chunxiao; Watt, Anthony; Solomonides, Ian; Thomas, Melissah Barnett (Journal of University Teaching and Learning Practice, 2025)
This qualitative study examines the impact of the Victoria University Block Model® on international postgraduate students’ educational experiences, aiming to understand its influence on student engagement, satisfaction, and academic achievement. Using a phenomenological approach, perceptions of eight international students enrolled in both traditional and Block mode units of study were analysed. Thematic analysis reveals five key themes: Assessment, Academic Engagement and Participation, Information Assimilation Time, Intensive Learning and Teaching, and Personal Mode Preference. The study highlights the significance of assessment structure on stress levels and academic outcomes. Despite the accelerated pace, small class sizes positively impact student engagement. While the VU Block Model® was generally favoured by students, individual preferences varied. The findings provide critical insights into the effects of delivery modes on international postgraduate students’ learning experiences, with implications for curriculum design and student engagement enhancement in higher education. Limitations include cohort specificity and small sample size, requiring further investigation.